SISTEM INFORMASI UMPAN BALIK PROSES BELAJAR MENGAJAR TERHADAP STAF PENGAJAR BERBASIS WEB PADA JURUSAN TEKNOLOGI INFORMASI POLITEKNIK NEGERI PADANG - Yulherniwati yulherniwati; Rasyidah rasyidah; Ronal Hadi; Rika Idmayanti (Elektron : Jurnal Ilmiah, 2012)
Feedback Information System Teaching and Learning Against Web-Based Teaching Staff In the Department of Information Technology Padang State Polytechnic is an information system that receives feedback from the learning process of students to teaching staff in the form of questionnaires, to then process and provide the necessary information. This system can be accessed by many users at the same time. Users of this system consists of students, operators, administrator, and faculty leaders. The system is built using PHP programming language and MySQL database server. This system could make it easier, save time and reduce errors in entering, process and provide information on the results of data processing questionnaires. While limitations are only limited to faculty assessment only and limited to the processing of assessment ratio.